All About That Face (No Trouble?) 'An Analysis of the Dutch Ban on Face-Covering Garments in Light of the ECHR, ICCPR and CEDAW, together with Feminist Theory' - Johanna Buerkert; Michaël Schut; Lili Szuhai (Utrecht Journal of International and European Law, 2021)
The Dutch ban on face-covering garments (BFG) has caused a considerable amount of debate in the Netherlands since its entry into force on August 1, 2019. Questions have been raised as to whether this law is discriminatory towards those who wear full-face veils for religious reasons, as these individuals, almost exclusively women, will be excluded from public life based on their religion. Inspired by this debate, this paper analyzes the Dutch BFG from a regional and international law perspective. More specifically, this paper seeks to analyze Dutch BFG in light of the European Convention on Human Rights, the International Covenant on Civil and Political Rights and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Additionally, feminist theories play an auxiliary role in specifying CEDAW obligations from a feminist perspective. While the ban may be justified from the point of view of the European Convention on Human Rights, it is problematic from the perspectives of the International Covenant on Civil and Political Rights and the Convention on the Elimination of All Forms of Discrimination against Women. Further research should therefore investigate this tension to determine how these frameworks can be reconciled while considering that the standard set by the European Court of Human Rights only provides a minimum level of protection.